Achieving of Country Image, Perceived Quality, and Brand Familiarity on Purchase Intention of Samsung Smartphone in Indonesia - Indriastuti, Herning; Irfan Maulana, Muhammad (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
The purpose of the study aims to analyze the influence of country image, perceived quality, and brand familiarity on the purchase intention of the Samsung smartphone in Indonesia. The sampling method used was a purposive sampling technique. Data sampling was obtained using 100 respondents. The data was collected by using a questionnaire given directly to the respondents. The analysis technique in this study used the Partial Least Square (PLS) data analysis method with the help of Smart-PLS 3 software. The results of this study indicate that country image has a negative and insignificant influence, while the perceived quality and brand familiarity have positive and significant influence on purchase intention